Long‐term serial angiographic outcomes after sirolimus‐eluting stent implantation1. Issue 1 (8th November 2012) - Ko, Euihong; Nasu, Kenya; Habara, Maoto; Tanaka, Nobuyoshi; Terashima, Mitsuyasu; Kinoshita, Yoshihisa; Tsuchikane, Etsuo; Asakura, Yasushi; Katoh, Osamu; Suzuki, Takahiko
Abstract Objective We evaluated, using quantitative coronary angiography, the natural history of change that occurred in target lesions after successful sirolimus‐eluting stent (SES) implantation. Background Percutaneous coronary intervention with drug‐eluting stents (DES) has significantly reduced the rate of repeated target lesion revascularization. However, early studies have raised concerns regarding the "late catch‐up" phenomenon of DES. Methods Between June 2004 and March 2007, consecutive 217 patients with 306 lesions without restenosis at early angiographic follow‐up underwent late angiographic follow‐up (early follow‐up: 11.2 ± 2.1 months and late follow‐up: 29.4 ± 5.2 months). Predictors of late catch‐up were identified with univariate and multivariate regression analyses. Results Although reference vessel diameter did not significantly change during follow‐up [3.15 mm (interquartile range (IQR): 2.81–3.49 mm), 3.12 mm (IQR: 2.79–3.47 mm), and 3.08 mm (IQR: 2.76–3.46 mm) at postprocedure, and early and late angiographic follow‐up, respectively; P = 0.2653], late loss (LL) significantly increased during follow‐up [0.05 mm (IQR: 0.00–0.13 mm) and 0.08 mm (IQR: 0.01–0.19 mm) at early and late follow‐up, respectively; P < 0.0001]. Univariate analysis showed previous intervention, adjunctive use of cutting balloon, lesion length, and progression of MLD, LL, %DS at early follow‐up as predictors of late catch‐up. Multivariate regression analysis identified %DS at early follow‐up as a predictor of late catch‐up (OR 1.076, CI 1.039–1.114, P < 0.0001). Conclusion Significant and continuous progression of neointima after SES implantation was observed in the present study. Larger LL may be a sign of late catch‐up phenomenon. © 2012 Wiley Periodicals, Inc.